Effectiveness of a sports energy e-module in hybrid learning for physical education students - Hendra Mashuri; Peby Gunarto; Luh Ita Mahendrayani; Taufik Rahman; M. Adam Mappaompo (Universitas Nusantara PGRI Kediri, 2026)
This study aims to examine the effectiveness of electronic modules on sports nutrition in sports nutrition courses. This study employed a quasi-experimental one-group pre-test–post-test design involving 60 physical education students enrolled in sports nutrition courses. The research instruments consisted of comprehension tests, affective assessments, and skills tests related to calculating energy and nutritional requirements. Data were analyzed using paired-sample t-tests. The results showed significant improvements in cognitive scores, t(59) = 16.16, p < 0.05, d = 2.281. There was an increase in students' affective t(59) = 7.70, p < 0.05, d = 0.97. There was an increase in students' skills t(59) = 28.99, p < 0.05, d = 5.692. These findings indicate that the use of the sports nutrition e-module was associated with improvements in students’ cognitive, affective, and skills scores during hybrid learning. The sports nutrition e-module may serve as a digital learning resource that supports competency development in sports nutrition learning contexts.